2023
DOI: 10.1002/cam4.5847
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress is involved in CRCI in breast cancer survivors via mediating cytokine levels

Abstract: Background Cancer‐related cognitive impairment (CRCI) is a frequent consequence in breast cancer survivors after chemotherapy and lowers their quality of life (QOL). Psychological distress is frequently experienced by breast cancer survivors. There are currently few studies investigating the role of psychological distress in the genesis of CRCI. Methods In total, 122 breast cancer survivors after standard chemotherapy within a year were recruited and assessed using the Psychological Distress Thermometer (DT). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
(74 reference statements)
0
3
0
Order By: Relevance
“…CRCI has multifactorial causes including depression, anxiety, and fatigue, which are also known to be associated with inflammation [ 42 , 49 51 ]. A recent study found that higher psychological distress indirectly predicted worse cognition through higher levels of IL-1β, TNF-α, and IL-4 [ 52 ]. In our study, we did not find a significant association between objective cognitive impairment and depression, anxiety, fatigue and, BMI (results not shown).…”
Section: Discussionmentioning
confidence: 99%
“…CRCI has multifactorial causes including depression, anxiety, and fatigue, which are also known to be associated with inflammation [ 42 , 49 51 ]. A recent study found that higher psychological distress indirectly predicted worse cognition through higher levels of IL-1β, TNF-α, and IL-4 [ 52 ]. In our study, we did not find a significant association between objective cognitive impairment and depression, anxiety, fatigue and, BMI (results not shown).…”
Section: Discussionmentioning
confidence: 99%
“…CRCI is documented most thoroughly to date in women with breast cancer (BC), which represents 22% of all cancer survivors in the United States ( 2 ). BC survivors have reported cognitive dysfunction for 5-10 years following treatment with chemotherapy and/or radiation therapy ( 7 , 14 ).…”
Section: Cancer Related Cognitive Impairmentmentioning
confidence: 99%
“…Known risk factors that increase incidence of CRCI after chemotherapy include non-cancer related comorbidities, anemia, and genetic predisposition ( 24 , 25 ). The proposed mechanisms for chemotherapy-associated CRCI include decreased neurogenesis, axonal degeneration and demyelination, reduction in dendrite volume and length, increased oxidative stress and free radical formation, neuroinflammation, toxicity to CNS progenitor cells, microglia apoptosis, blood brain barrier disruption, brain blood flow alterations, myelin degradation, production of damage associated molecular patterns, cytokine-induced neurotoxicity, reduced glucose metabolism, alteration in brain water content, and fluctuations in neurotransmitter levels ( 5 , 14 , 22 , 23 , 25 , 26 ). Select chemotherapy drugs, including 5-fluorouracil (5-FU), carmustine (BCNU), lomustine (CCNU), temozolomide (TMZ) cross the intact blood brain barrier to directly injure the brain.…”
Section: Cancer Related Cognitive Impairmentmentioning
confidence: 99%
“…Despite the frequent diagnosis of breast cancer, mortality rates have either remained stable or decreased since the 1990s, due to advanced early detection and treatment methods (3). However, breast cancer patients experience varying degrees of psychological distress during both the pre-treatment and posttreatment processes (4). Spirituality, in this context, is an important source of strength and coping for cancer patients to adapt to their illness (5).…”
Section: Introductionmentioning
confidence: 99%